2017
DOI: 10.4088/jcp.16m10876
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors and Mental Health Outcomes of First Suicide Attempt During Childhood and Adolescence

Abstract: Suicide attempts in children and adolescents substantially differ in contributing factors and adulthood mental health outcomes. Preventing childhood maltreatment and early intervention for psychiatric disorders may have broad benefits to reduce not only the suffering of these children and adolescents, but also the burden of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 0 publications
4
23
1
6
Order By: Relevance
“…Mirroring the situation in adults, female adolescents have a higher rate of self-harm and suicide attempts, but a lower rate of suicide [ 3 ]. Our data confirm that the male-to-female ratio of suicide is increasing from prepubescent children to adolescents [ 18 ]. Another risk factor known from suicide in adults is living in rural areas [ 34 36 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Mirroring the situation in adults, female adolescents have a higher rate of self-harm and suicide attempts, but a lower rate of suicide [ 3 ]. Our data confirm that the male-to-female ratio of suicide is increasing from prepubescent children to adolescents [ 18 ]. Another risk factor known from suicide in adults is living in rural areas [ 34 36 ].…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies found differences in the possible factors triggering suicide between younger and older adolescents: suicides in adolescents younger than 15 have often been associated with family conflicts, maltreatment or problems at school, while romantic relationships and psychiatric illness were more common risk factors in older adolescents [ 7 , 16 18 ]. Brothers and sisters may be an important source of support in parent–child conflicts, which might explain the association with only children found in this study among younger adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should also further investigate the more elusive subjective aspects of suicide risk, such as SI, as well as implicated psychological constructs such as hopelessness, rumination, and anhedonia [209][210][211], which may be relevant across diagnoses. Similarly, social experiences such as childhood maltreatment and peer bullying form a strong prelude to STB in later life [208,212,213], and impact on the neural structures implicated in STB (e.g., DMPFC structure and function [214,215]). Therefore, adverse experiences should be taken into account in future studies on the neurobiology of STB.…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, as a result of the traditional Chinese culture's strong stigma toward psychiatric disorders, the serious shortage of psychiatrists and infrastructure (especially in the rural areas) and low mental health literacy, only 8.3 to 27.6% of patients with depressive disorders are diagnosed, and about half of those diagnosed receive effective treatment [16]. Adolescence is the stage in which most mental health problems first manifest [17]. Researches also suggest that delays in seeking help for mental health problems lead to poorer treatment outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%